2006
DOI: 10.1111/j.1600-0854.2006.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Hook2 Localizes to the Centrosome, Binds Directly to Centriolin/CEP110 and Contributes to Centrosomal Function

Abstract: Centrosomes serve as microtubule‐organizing centers. However, centrosome function depends on microtubule organization and protein transport because the formation, positioning and maintenance of centrosomes require microtubule‐dependent retrograde transport. Linker proteins that associate with the motor protein dynein, organelles and microtubules facilitate loading of cargos for retrograde transport and thus contribute to the composition and placement of the centrosome and other juxtanuclear protein complexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 36 publications
11
85
0
Order By: Relevance
“…6B), perhaps because of dissociation from the complex during the procedure or the existence of alternative FHF assemblies. The existence of FHF variants would be consistent with reported differences in the intracellular localization and function of the three Hook subunit isoforms (64,66,67). These results demonstrated that a mammalian FHF complex comprised of at least Hook1, Hook3, and FHIP has the biochemical properties of a bona fide Rab5 effector.…”
Section: Rab5 Is Required For Somatodendritic Sorting Of Glutamate Resupporting
confidence: 87%
“…6B), perhaps because of dissociation from the complex during the procedure or the existence of alternative FHF assemblies. The existence of FHF variants would be consistent with reported differences in the intracellular localization and function of the three Hook subunit isoforms (64,66,67). These results demonstrated that a mammalian FHF complex comprised of at least Hook1, Hook3, and FHIP has the biochemical properties of a bona fide Rab5 effector.…”
Section: Rab5 Is Required For Somatodendritic Sorting Of Glutamate Resupporting
confidence: 87%
“…One study found that Hook1 can specifically interact with clathrin-independent endocytosis cargo proteins for recycling tubules from early endosomes but not other clathrinindependent endocytosis cargo proteins (24). Hook3 has been linked to scavenger receptor A to participate in the endocytotic turnover of the receptor (44), whereas Hook2 has been suggested to interact with centriolin/CEP110 to maintain centrosomal structure (23). These unique protein interactions through the C terminus of Hook proteins might provide enough specificity to regulate these adaptors to modulate motors for particular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Each isoform has been associated with a different cargo. Hook3 localizes to the Golgi (19), Hook2 is recruited to centrosomes (23), and Hook1 is implicated in endosomal transport (24 -26). To explore adaptors with roles in cargo transport, we focused on Hook1 and Hook3 in our studies.…”
mentioning
confidence: 99%
“…(23) Reports of assessing centrosomal abnormalities by profiling tubulin gene expression are few, and most of these evaluated tubulin protein expression. (24,25) Schneeweiss et al (26) examined centrosomal protein expression in 103 primary invasive breast cancer tissues using IHC technique and found that centrosomal aberrations were associated with the factors predicting a more aggressive course of disease. In this study, we investigated centrosomal abnormality in the sequence of NBT, ADH/PPAH, DCIS and IDC by assessing α and γ-tubulins at the DNA, mRNA transcription and protein expression levels, and γ-tubulin antibody specifically labeled centrosomes by immunohistochemical staining technique in paraffin-embedded tissue sections was used for validation.…”
Section: Discussionmentioning
confidence: 99%